Decreased fracture incidence with traditional Chinese medicine therapy in patients with osteoporosis: a nationwide population-based cohort study - Yu-Chi Wang; Jen-Huai Chiang; Hsin-Cheng Hsu; Chun-Hao Tsai (BMC, 2019)
Abstract Background There are no published studies regarding the efficacy of traditional Chinese medicine (TCM) for the prevention of osteoporotic fracture. Therefore, we conducted this nationwide, population-based cohort study to investigate the probable effect of TCM to decrease the fracture rate. Methods We identified cases with osteoporosis and selected a comparison group that was frequency-matched according to sex, age (per 5 years), diagnosis year of osteoporosis, and index year. The difference between the two groups in the development of fracture was estimated using the Kaplan-Meier method and the log-rank test. Results After inserting age, gender, urbanization level, and comorbidities into the Cox's proportional hazard model, patients who used TCM had a lower hazard ratio (HR) of fracture (adjusted HR: 0.47, 95% CI: 0.37-0.59) compared to the non-TCM user group. The Kaplan-Meier curves showed that osteoporosis patients who used TCM had a lower incidence of fracture events than those who did not (p < 0.00001). Our study also demonstrated that the longer the TCM use, the lesser the fracture rate. Conclusion Our study showed that TCM might have a positive impact on the prevention of osteoporotic fracture.